2012
DOI: 10.1111/j.1471-6712.2012.01086.x
|View full text |Cite
|
Sign up to set email alerts
|

Social identity and stroke: ‘they don't make me feel like, there's something wrong with me’

Abstract: Over 85% of the people survive stroke; and of those, over 80% are discharged to the community. However, the majority do not recover completely. Loss of identity is a commonly reported experience after stroke. Studies focus on the individual survivors' use of their own cognitive resources to adapt to change, rather than examining the effects of social interactions on stroke survivors' identities. Social relationships are the foundation upon which survivors rebuild skills to engage with the world, yet little is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 56 publications
(120 reference statements)
0
81
0
Order By: Relevance
“…This lack of improvement in social QOL has previously been observed in the literature. 37,38 After a stroke, relationships with friends and colleagues decline, resulting in stroke survivors living more isolated lives than before the stroke. Similarly, environmental QOL, which focuses on issues regarding living conditions, are unlikely to vary for most stroke survivors and may in fact be amplified because of the stroke.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of improvement in social QOL has previously been observed in the literature. 37,38 After a stroke, relationships with friends and colleagues decline, resulting in stroke survivors living more isolated lives than before the stroke. Similarly, environmental QOL, which focuses on issues regarding living conditions, are unlikely to vary for most stroke survivors and may in fact be amplified because of the stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Third, social interaction was highlighted throughout our data and the findings suggest that being part of a social network, finding a sense of community and belonging in a positive and supportive environment will in turn lead to increased/sustained attendance. This is supported by Anderson and Whitfield (2013) who argued that social relationships are the foundation on which stroke-survivors rebuild their skills to engage with the world. Other studies have also confirmed that social support in group sessions is important in sustaining commitment by participants (Desrosiers et al 2008).…”
Section: Discussionmentioning
confidence: 66%
“…A social group, where participants are treated as 'us' rather than the individual, provides attendees with a sense of belonging and purpose (Anderson and Whitfield 2013). Five of the six participants in this study preferred to exercise in a group setting rather than one-on-one with their therapist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With more people experiencing stroke, the need for rehabilitation services that enable stroke survivors and their families to transition back to healthy community living will also increase. Currently, 80% of survivors of stroke are discharged to the community [2]. However, as stroke survivors return home after medical care, they find themselves confronted by their physical and social limitations [3].…”
Section: Introductionmentioning
confidence: 99%